Biblical education: An introduction - Bagrowicz, Jerzy (Acta Universitatis Nicolai Copernici Pedagogika, 2020)
The Old and the New Testaments are not only the word of God and a source of wisdom that leads to salvation, but also a mine of knowledge and educational wisdom. One can speak of biblical pedagogy which in a sense is a synthesis of God’s wisdom revealed to the people of Israel and their educational experience which they gained in the centuries of their existence. Both the Old and the New Testaments, in their entirety, are a source of this pedagogy adopted by God with respect to the Chosen People as a whole and as individuals. For the educational practice of Christianity, the basic code of ethical norms contained in the Ten Commandments, i.e. the Decalogue, is of particular importance, applying to all believers. These are the rules of conduct that provide the basis in the formation and education of a new person. One cannot understand the principles of education based on the teachings of Jesus Christ without exploring the educational tradition of Israel and comprehending the pedagogy contained in the Old Testament. Jesus Christ did not reject this tradition. He used it to build on it, revealing its much broader and deeper perspective. The biblical pedagogy continues to be valid also in the conditions of the modern world.